POTENSI EKOWISATA BERBASIS BUDAYA KAMPUNG BETING DI TEPIAN SUNGAI KAPUAS KOTA PONTIANAK - Yumanraya Noho; Ade Abriansyah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
The goal of this study is to figure out the cultural potencies of Kampung Beting village that located in the Kapuas riverbank, East Pontianak District, Pontianak City, West Kalimantan as a tourism area by using culture-based ecotourism approach. To describe the potential culture, writer used some factors as a parameter they are of historical value, harmony / alignment, uniqueness, social function, appeal, rarity and some aspects that support the cultural potencies such as environmental conditions, infrastructure, facilities, accessibility, communities, and government attitudes. The results showed that the most of Kampung Beting’s cultural heritages are potential to be a culture based ecotourism appeal. It is apparent from the historical values, alignment/harmony, uniqueness, charm and preserved scarcity of building Kadriyah Kraton Palace, the Jami mosque, the settlement on the water, and Festival Meriam Karbit. In other side, some of them become shifting in social functioning and appeal due to lack of maintenance and care by local communities and government.